Определение научно, технологически и экономически обоснованных требований к показателям качества сырья для конкретного технологического процесса - Кац, Марк Давидович; Беккер, М. А.; Давиденко, А. М. (Eastern-European Journal of Enterprise Technologies, 2014)
Presently there is a serious problem, related to large methodical difficulties, arising up at the attempts of determination of correct requirements to quality of raw material for a certain technological process It is proved by an imitation design, that the method of renewal of odnomernykh de-pendences allows to decide the task of determination scientifically, technologically and the economic grounded requirements to optimum poddiapazonam values of neu-pravlyaemykh parameters (to the indexes of quality of raw material) for a concrete technological process.